Two-Dimensional Correlation Function of Binary Black Hole Coalescences - Marco Cavaglià; Ashini Modi (Universe, 2020)
We compute the two-dimensional correlation functions of the binary black hole coalescence detections in LIGO-Virgo’s first and second observation runs. The sky distribution of binary black hole coalescence events is tested for correlations at different angular scales by comparing the observed correlation function to two reference functions that are obtained from mock datasets of localization error regions uniformly distributed in the sky. No excess correlation at any angular scale is found. The power-law slope of the correlation function is estimated to be <semantics> γ = 2.24 ± 0.33 </semantics> at the three- <semantics> σ </semantics> confidence level, a value consistent with the measured distribution of galaxies.